Órgãos genitais e osso medular na maturidade sexual e no ciclo de formação do ovo em codornas japonesas - Andrade, Kassiana Germani (2018)
Two experiments were carried out to evaluate the development of genital organs and bone marrow in sexual maturity and in the daily egg-laying cycle formation Japanese quail. The experiment I, described the changes during daily egg-cycle formation in Japanese quail. Sixty quails (18 wks old) were distributed in 6 treatments according to the egg-cycle formation: 0, 2, 4, 8, 14 and 20hs post oviposition. There were analyzed the serum biochemistry, morphological aspects of genital organs and bones strength variables (femur and tibiotarsus). The magnum had relative weight higher in the periods before ovulation (20hs and 0h). However histologically, the height and width of the magnum and uterus folds had no significant difference, but tubular glands in magnum showed variation in its functionally through periods, with abundant eosinophilic and PAS+ content at 2hs and empty aspect at 4hs post oviposition. The mucosa epithelium presented ciliated and secretory cells (1:1). Phosphorus, alkaline phosphatase and ionic calcium did not vary with the periods, while albumin and total calcium had a higher value with 2hs post oviposition and were lower in 8 and 14hs, respectively. For bone analysis, the bone strength and weight variables remained unchanged during the daily egg-laying cycle. The bone mineral density (mmAl) of the femur and tibiotarsus presented lower mean at 2hs and higher at 14hs post oviposition. There were no differences in bones cortical variables in both bones. However, in the medullary bone there were differences for Ca%, with lower means at 14hs after post oviposition, coinciding with the active phase in uterus (palisade layer formation), which in the quails corresponds to the nocturnal period and early morning (06h00). The higher means of Ca % was at 0h post oviposition (16h00). This finding may indicate a recovery of minerals reserve in medullary bone in the inactivity phase of the uterus, preparing it to next egg-cycle. The oviduct of Japanese quail had morphological changes in consequence of the daily egg-cycle as well as the concentration of serum calcium and the calcium content of the medullary bone of the femur and tibiotarsus, keeping the calcium requirement and homeostasis during daily egg-cycle. The experiment II, the objective was to describe the medullary bone formation and the genital organ development in sexual maturity under the effect of two light programs, with different light/dark periods, simulating the winter and summer seasons in Maringá (11L:13D and 14L:10D), in 550 females quails of 1 to 35 days old housed in 10 battery cages (0.80 x 0.80 m) in a climatic chamber with controlled light and temperature. From 35 days, 30 min of light were added every 3 days until reaching 17L:7D. Blood, bone and genital organs were collected at 17, 21, 25, 28, 31, 35, 42, 49, 56, 63 and 70 days in 5 birds per treatment, as well as the feed intake was observed weekly. The quail posture under the 11L:13D light program was higher than the 14L:10D light program, with 47.89 and 32.11%, respectively. Sexual maturity is characterized by a number of metabolic events. Serum levels of albumin and calcium increase immediately before sexual maturity. Albumin participates in the transport of substances from liver to the growing follicles in the ovary. Calcium, on the other hand, influences the formation of eggshell and medullary bone. The birds under the 11L:13D light program showed genital organs development earlier than the 14L:10D light program, with relative ovary weight higher at 56 days and oviduct at 42 days and oviduct length was longer at 56 days. Consequently, they started laying earlier. The medullary bone developed first in the femur, and its only function is to provide calcium for egg shell formation